Análisis de la cultura afroecuatoriana desde la perspectiva de los medios de prensa escrita, revista Vistazo y el comercio entre el período de enero a junio de 2013. - Célleri Cabezas, Erika Alexandra (2014)
This job brings to the stage, an investigation of the Afro-Ecuadorian culture, and their relationship to football focusing an intercultural approach by the media Glance such as “Vistazo” Magazine, and the Newspaper “El Comercio”. This will determine, somehow the intercultural exercise of media, should be managed by, the Organic Law of Communication (LOC) where the Ecuadorian society should not be exempted. We pretend with this intend with this, to confirm the hypothesis of this problem. The result to delimit this research was taken during the final period of qualifying to the last world cup of Brazil, between July and December 2013 , in fact of dependent variable to analyze the discourse of two independent writings, that means demarcates the analysis from multiculturalism.